Pemberdayaan Masyarakat di Desa Kedungotok Melalui Pelatihan Kerajinan Tangan dari Barang Bekas - Ino Angga Putra; Yesika Febriani; Rifka Aulia Nur Rohmah; Vera Fikrotin (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this community service activity is to a) increase the insight/knowledge of teenagers in utilizing used goods into valuable items and b) improve the skills of teenagers in making handicrafts from used goods. Approach methods for implementing community service activities include lecture and training methods. The lecture and training methods are carried out on training activities for handicrafts from used goods. There are 3 stages of community service implementation, namely a) coordination with partners, b) preparation of training tools and materials, and c) implementation of training activities. The implementation of this activity was attended by 25 people (teenagers) and took place at the Posyandu Dusun Kedungboto, Kedungotok Village, Tembelang District. Data collection in this community service activity is carried out through an assessment of the skills of the participants. The results of the implementation of community service activities were obtained: a) the skills of the youth of Kedungboto Hamlet, Kedungotok Village, Tembelang Jombang District, classified as "High" category where 76% of the participants were in the high category and 24% of the participants were in the sufficient category and b) the skill assessment of the youth of Kedungboto Hamlet, Kedungotok Village, District Tembelang Jombang also showed a high score, namely the average skill value of the participants was also at a high score wherein the aspect of the ability to understand handicraft tools and materials a score of 3.2 was obtained. In the aspect of the ability to make handicrafts, a score of 3.4 is obtained and the aspect of the ability to package handicrafts has obtained a value of 3.5. The results of community service activities that have been made by the youth, namely the product of the scarf hanger and tissue holder, are expected to be widely marketed and become the flagship product of Kedungotok Village in increasing the income and economic value of the people of Kedungotok Village, Tembelang Jombang District.